High-strength anti-freezing concrete and preparation process thereof

By preparing high-strength freezing concrete, using specific process steps and material combinations, the problem of reducing compressive strength loss and durability of concrete during freezing and thawing is solved, and higher compressive strength and freezing resistance are achieved.

CN119430760APending Publication Date: 2025-02-14克州顺鑫商品混凝土有限责任公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411579079.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Existing concrete is prone to loss of compressive strength and reduced durability during freezing and thawing. It is mainly because the expansion pressure caused by water freezing exceeds the cohesion of the concrete, resulting in cracks.

Method used

By preparing high-strength anti-freeze concrete, specific process steps are adopted, including the preparation of components A and component B, and the addition of composite admixtures. In component A, powdered crystals are prepared using materials such as thiourea and salicyle, and are uniformly dispersed with materials such as phosphomolybdic acid and octylphenyl polyoxyethylene ether, and then added to sodium polyacrylate solution after forming a dispersion; Rice husk ash, basalt fibers, chopped basalt fibers and calcium sulfate whiskers are added to B to improve the degree of interface bonding between the aggregate and the cement slurry. The composite admixture forms a structure that can rupture and release the repair agent during freeze-thawing process through heating reaction and curing treatment.

Benefits of technology

Through the above process, the compressive strength and freezing durability of concrete are improved, the generation and expansion of microcracks during freeze-thawing process are reduced, and the overall performance of concrete is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention provides high-strength anti-freezing concrete and a preparation process thereof, and belongs to the technical field of concrete. The preparation process comprises the following steps: preparing the component A; preparing a urea resin prepolymer; preparing a composite admixture; preparing a component B; and mixing the component A and the component B, and adding a composite additive. The preparation method comprises the following steps: dissolving thiosemicarbazide and salicylaldehyde in methanol, carrying out a heating reaction, condensing and crystallizing to prepare powdery crystals, adding the powdery crystals into an aqueous solution of phosphomolybdic acid, adding octyl phenyl polyoxyethylene ether, uniformly dispersing to prepare a dispersion liquid, and finally adding the dispersion liquid into a sodium polyacrylate solution to prepare a component A; when the component A is added into concrete, the dispersion and hydration of the concrete can be promoted, a plurality of crystal sites are established, and the particle sizes of C-S-H gel and acicular ettringite are homogenized and densified, so that the compressive strength and the anti-freezing durability of the concrete are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of concrete, and in particular to high-strength frost-resistant concrete and a preparation process thereof. Background Art

[0002] Concrete is one of the important raw materials in construction projects. It is made of cementitious materials, aggregates (including fine aggregates such as sand and coarse aggregates such as gravel), water, and admixtures and additives added as needed, in a certain proportion. In the most common form, cement is used as a cementitious material, which can undergo a chemical reaction (i.e., the hydration process) after mixing with water and gradually harden, thereby bonding the loose aggregates into a solid whole.

[0003] There are a large number of pores in concrete, which become places for water to expand when water freezes. When water turns into ice, its volume increases by about 9%. This expansion pressure can exceed the cohesion inside the concrete, leading to the formation of microscopic or even macroscopic cracks, causing the loss of compressive strength of the concrete. Repeated freezing and thawing of concrete will aggravate this process, ultimately damaging the concrete structure and affecting its durability.

[0004] Therefore, we proposed a high-strength frost-resistant concrete with good frost resistance and its preparation process to improve the durability of concrete. Summary of the invention

[0005] In view of the deficiencies in the prior art, the present invention aims to provide a high-strength frost-resistant concrete and a preparation process thereof.

[0006] A preparation process of high-strength frost-resistant concrete comprises the following steps:

[0007] S1: Preparation of component A

[0008] S1.1: Add thiosemicarbazide and salicylaldehyde to methanol in a molar ratio of 1:(1.2-1.4), stir to dissolve, and mix thoroughly to obtain a mixed solution;

[0009] S1.2: heating the mixed solution at 70-80°C while stirring to condense and crystallize, collecting the precipitated crystals by filtration, washing and drying to obtain powdery crystals;

[0010] S1.3: Dissolve phosphomolybdic acid in deionized water at a solid-liquid ratio of 1 g: (25-35) mL, add the above powdered crystals, disperse by ultrasonic vibration for 30-40 min, add octylphenyl polyoxyethylene ether, and continue ultrasonic dispersion for 20-30 min to obtain a dispersion;

[0011] S1.4: Heat acrylic acid to 50-60°C, then add sodium hydroxide solution and ammonium persulfate while stirring, and react for 10-12 hours to obtain a sodium polyacrylate solution;

[0012] S1.5: Add the above dispersion to the above sodium polyacrylate solution in a volume ratio of 1:(8-12), then add dilute sulfuric acid to adjust the pH to 5.5-6.5, and stir for 1-2 hours to obtain component A;

[0013] S2: Preparation of urea-formaldehyde resin prepolymer

[0014] Mix urea and 35% formaldehyde solution in a mass ratio of 1: (2.5-3.5) and stir to dissolve, then add triethanolamine to adjust the pH to 8-9, then heat and stir under reflux at 70-80° C. for 40-50 hours to obtain a urea-formaldehyde resin prepolymer;

[0015] S3: Preparation of composite admixtures

[0016] Polyvinyl alcohol, epoxy resin, deionized water and n-octanol are dispersed and mixed at high speed, and then the urea-formaldehyde resin prepolymer is added, fully mixed and heated for reaction, and then NH4Cl, deionized water and resorcinol are added, stirred and solidified, and finally sodium carbonate solution is added, and the composite admixture is obtained after standing and stratifying, washing and drying;

[0017] S4: Preparation of component B

[0018] Mixing cement, fly ash, crushed stone, river sand, polycarboxylate-based water reducer, water, rice husk ash, basalt fiber, chopped basalt fiber and calcium sulfate whisker to obtain component B;

[0019] S5: Mix component A and component B and add composite admixture

[0020] The above component A is added to the component B in a mass ratio of 1:(8-10), and then the above composite admixture is added, and the mixture is fully stirred to obtain high-strength frost-resistant concrete.

[0021] Furthermore, S3 specifically includes the following steps:

[0022] S3.1: Add polyvinyl alcohol and epoxy resin into deionized water in a mass ratio of 1: (3-5): (60-80), stir for 20-30 min, add n-octanol and place in a high-speed dispersing homogenizer and disperse at a rate of 5000-6000 r / min for 30-40 min to obtain an emulsion;

[0023] S3.2: The urea-formaldehyde resin prepolymer prepared in step S2 and the above emulsion are stirred at a rate of 400-500 r / min for 1-2 h in a volume ratio of 1:(10-16), and then heated to 70-80°C for reaction for 3-4 h to obtain intermediate A;

[0024] S3.3: Add NH4Cl to the intermediate A, adjust the pH to 3-4, then add deionized water and resorcinol, stir for 2-3 hours, and solidify to obtain intermediate B;

[0025] S3.4: Add sodium carbonate solution to the intermediate B to adjust the pH to 7-8, cool naturally to room temperature and stand to separate the layers, remove the upper aqueous phase, then wash the lower precipitate with deionized water 3-4 times, and dry to obtain a composite admixture.

[0026] Furthermore, S4 specifically includes the following steps:

[0027] S4.1: Add cement, fly ash, crushed stone and river sand into a concrete mixer and stir for 20-30 minutes to fully disperse and mix;

[0028] S4.2: Add polycarboxylate water reducer and water into the concrete mixer and continue stirring for 15-25 minutes to mix thoroughly;

[0029] S4.3: Add rice husk ash, basalt fiber, chopped basalt fiber and calcium sulfate whisker into a concrete mixer and continue mixing for 20-30 minutes to obtain component B.

[0030] Furthermore, the solid-liquid ratio of thiosemicarbazide to methanol is 1 g: (20-30) mL.

[0031] Furthermore, the mass ratio of powdered crystals to phosphomolybdic acid is (1.1-1.5):1, the mass ratio of octylphenyl polyoxyethylene ether to phosphomolybdic acid is 1:(16-20), the molar ratio of sodium hydroxide to acrylic acid is (1-3):1, the solid-liquid ratio of ammonium persulfate to sodium hydroxide solution is 1g:(55-65)mL, and the concentration of sodium hydroxide solution is 0.1-0.3mol / L.

[0032] Furthermore, the mass ratio of n-octanol to epoxy resin is 1:(35-45).

[0033] Furthermore, the volume ratio of deionized water to intermediate A is 1:(3-5), and the solid-liquid ratio of resorcinol to deionized water is 1 g:(15-25) mL.

[0034] Further, in parts by weight, component B includes: 230-320 parts of cement, 80-100 parts of fly ash, 600-700 parts of crushed stone, 500-600 parts of river sand, 160-180 parts of rice husk ash, 70-80 parts of basalt fiber, 35-45 parts of chopped basalt fiber, 65-95 parts of calcium sulfate whisker, 10-20 parts of polycarboxylate water reducer and 150-300 parts of water.

[0035] Furthermore, the amount of the composite admixture added is 180-220 parts by weight.

[0036] A high-strength frost-resistant concrete is prepared by any of the above-mentioned processes for preparing high-strength frost-resistant concrete.

[0037] Compared with the prior art, the present invention has the following beneficial effects:

[0038] 1. The present invention first dissolves thiosemicarbazide and salicylaldehyde in methanol, heats them for reaction and condenses them for crystallization to obtain powder crystals, then adds the powder crystals into an aqueous solution of phosphomolybdic acid, adds octylphenyl polyoxyethylene ether to uniformly disperse them into a dispersion, and finally adds the dispersion into a sodium polyacrylate solution to obtain component A. Component A is added into concrete, and its chain sodium polyacrylate has a dispersing effect, which can promote the dispersion and hydration of concrete. The hybrid polyhedral structure of the powder crystals and phosphomolybdic acid serves as an adsorption nucleation center to establish multiple crystallization sites, so that the particle sizes of CSH gel and needle-shaped ettringite are uniform and dense, thereby improving the compressive strength and frost resistance of concrete.

[0039] 2. The present invention prepares a urea-formaldehyde resin prepolymer by mixing urea and formaldehyde solution, then adds epoxy resin and polyvinyl alcohol into deionized water, disperses them into an emulsion at high speed, and then mixes the urea-formaldehyde resin prepolymer and the emulsion, heats them and reacts them to prepare a composite admixture. After the composite admixture is added to concrete, when the concrete is subjected to freezing and thawing, the admixture can be broken in time to release a repair agent to fill the microcracks generated by freezing and thawing of the concrete, thereby further improving the anti-freeze durability of the concrete.

[0040] 3. The present invention helps to improve the compressive strength of concrete by adding rice husk ash, basalt fiber, chopped basalt fiber and calcium sulfate whisker to concrete. The simultaneous addition of basalt fiber, chopped basalt fiber and calcium sulfate whisker helps to improve the interface bonding between aggregate and cement paste, optimize the internal pore structure of concrete, form a denser microstructure, reduce the penetration of water in the environment into the interior of concrete, reduce the frost heave pressure caused by the freezing of free water in the concrete, thereby improving the anti-freeze durability of concrete. DETAILED DESCRIPTION

[0041] The following is a detailed description of a high-strength frost-resistant concrete and its preparation process provided by the present invention in conjunction with specific embodiments. At the same time, it is explained here that in order to make the embodiments more detailed, the following embodiments are the best and preferred embodiments, and those skilled in the art may also adopt other alternatives to implement some known technologies; and it is only for a more specific description of the embodiments, and is not intended to specifically limit the present invention.

[0042] Example 1

[0043] A preparation process of high-strength frost-resistant concrete comprises the following steps:

[0044] S1: Preparation of component A

[0045] Add thiosemicarbazide and salicylaldehyde to methanol in a molar ratio of 1:1.2, stir to dissolve, and mix thoroughly to obtain a mixed solution, wherein the solid-liquid ratio of thiosemicarbazide to methanol is 1g:20mL, then heat the mixed solution at 70°C, stir to condense and crystallize, filter and collect the precipitated crystals, wash and dry to obtain powdery crystals, then dissolve phosphomolybdic acid in deionized water at a solid-liquid ratio of 1g:25mL, add the powdery crystals, disperse by ultrasonic vibration for 30min, add octylphenyl polyoxyethylene ether, and continue ultrasonic dispersion for 20min to obtain the separation. dispersion for standby use, wherein the mass ratio of powdered crystals to phosphomolybdic acid is 1.1:1, and the mass ratio of octylphenyl polyoxyethylene ether to phosphomolybdic acid is 1:16, and then the acrylic acid is heated to 50°C, and then sodium hydroxide solution and ammonium persulfate are added while stirring, and the reaction is carried out for 10 hours to obtain a sodium polyacrylate solution for standby use, wherein the molar ratio of sodium hydroxide to acrylic acid is 1:1, and the concentration of the sodium hydroxide solution is 0.1 mol / L, and finally, the dispersion is added to the sodium polyacrylate solution at a volume ratio of 1:8, and then dilute sulfuric acid is added to adjust the pH to 5.5, and stirred for 1 hour to obtain component A;

[0046] S2: Preparation of urea-formaldehyde resin prepolymer

[0047] Urea and 35% formaldehyde solution were mixed and stirred in a mass ratio of 1:2.5 to dissolve, and triethanolamine was added to adjust the pH to 8, and then heated and stirred at 70°C for 40 hours to reflux to obtain a urea-formaldehyde resin prepolymer;

[0048] S3: Preparation of composite admixtures

[0049] Polyvinyl alcohol and epoxy resin were added to deionized water at a mass ratio of 1:3:60, stirred for 20 minutes, and then n-octanol was added and placed in a high-speed dispersing homogenizer for 30 minutes at a rate of 5000r / min to obtain an emulsion, wherein the mass ratio of n-octanol to epoxy resin was 1:35, and then the urea-formaldehyde resin prepolymer and the emulsion were stirred at a rate of 400r / min for 1 hour at a volume ratio of 1:10, fully mixed, and then heated to 70°C for reaction for 3 hours to obtain intermediate A. After that, NH4Cl was added to the intermediate A to adjust the pH to 3, and then deionized water and resorcinol were added, stirred for 2 hours, and solidified to obtain intermediate B, wherein the volume ratio of deionized water to intermediate A was 1:3, and the solid-liquid ratio of resorcinol to deionized water was 1g:15mL. Finally, sodium carbonate solution was added to the intermediate B to adjust the pH to 7, and the mixture was naturally cooled to room temperature and allowed to stand for stratification, the upper aqueous phase was removed, and then the lower precipitate was washed with deionized water for 3 times, and dried to obtain a composite admixture;

[0050] S4: Preparation of component B

[0051] By weight, 230 parts of cement, 80 parts of fly ash, 600 parts of crushed stone and 500 parts of river sand were added to a concrete mixer, stirred for 20 minutes, and fully dispersed and mixed, then 10 parts of polycarboxylate water reducer and 150 parts of water were added to the concrete mixer, and stirred for 15 minutes and fully mixed, and finally, 160 parts of rice husk ash, 70 parts of basalt fiber, 35 parts of chopped basalt fiber and 65 parts of calcium sulfate whisker were added to the concrete mixer, and stirred for 20 minutes to obtain component B;

[0052] S5: Mix component A and component B and add composite admixture

[0053] The above component A is added to the component B in a mass ratio of 1:8, and then 180 parts by weight of the above composite admixture is added, and the mixture is fully stirred and mixed to obtain high-strength frost-resistant concrete.

[0054] Example 2

[0055] A preparation process of high-strength frost-resistant concrete comprises the following steps:

[0056] Add thiosemicarbazide and salicylaldehyde to methanol in a molar ratio of 1:1.3, stir to dissolve, and mix thoroughly to obtain a mixed solution, wherein the solid-liquid ratio of thiosemicarbazide to methanol is 1g:25mL, and then heat the mixed solution at 75°C, stir to condense and crystallize, filter and collect the precipitated crystals, wash and dry to obtain powdery crystals, then dissolve phosphomolybdic acid in deionized water at a solid-liquid ratio of 1g:30mL, add the powdery crystals, and after ultrasonic vibration dispersion for 35min, add octylphenyl polyoxyethylene ether, and continue ultrasonic dispersion for 25min to obtain a dispersed liquid for standby use, wherein the mass ratio of powdered crystals to phosphomolybdic acid is 1.3:1, and the mass ratio of octylphenyl polyoxyethylene ether to phosphomolybdic acid is 1:18, and then the acrylic acid is heated to 55°C, and then sodium hydroxide solution and ammonium persulfate are added while stirring, and the reaction is performed for 11 hours to obtain a sodium polyacrylate solution for standby use, wherein the molar ratio of sodium hydroxide to acrylic acid is 2:1, and the concentration of the sodium hydroxide solution is 0.2 mol / L, and finally, the dispersion is added to the sodium polyacrylate solution at a volume ratio of 1:10, and then dilute sulfuric acid is added to adjust the pH to 6, and stirred for 1.5 hours to obtain component A;

[0057] S2: Preparation of urea-formaldehyde resin prepolymer

[0058] Urea and 35% formaldehyde solution were mixed and stirred in a mass ratio of 1:3 to dissolve, and triethanolamine was added to adjust the pH to 8.5, and then heated and stirred at 75°C for 45 hours to reflux to obtain a urea-formaldehyde resin prepolymer;

[0059] S3: Preparation of composite admixtures

[0060] Polyvinyl alcohol and epoxy resin were added to deionized water at a mass ratio of 1:4:70, stirred for 25 minutes, and then n-octanol was added and placed in a high-speed dispersing homogenizer for dispersion at a rate of 5500r / min for 35 minutes to obtain an emulsion, wherein the mass ratio of n-octanol to epoxy resin was 1:40, and then the urea-formaldehyde resin prepolymer and the emulsion were stirred at a rate of 450r / min for 1.5 hours at a volume ratio of 1:13, fully mixed, and then heated to 75°C for reaction for 3.5 hours to obtain intermediate A, and then , add NH4Cl to intermediate A, adjust the pH to 3.5, then add deionized water and resorcinol, stir for 2.5 hours, solidify to obtain intermediate B, wherein the volume ratio of deionized water to intermediate A is 1:4, and the solid-liquid ratio of resorcinol to deionized water is 1g:20mL, finally add sodium carbonate solution to intermediate B to adjust the pH to 7.5, cool naturally to room temperature and stand for stratification, remove the upper aqueous phase, then wash the lower precipitate with deionized water 3 times, and dry to obtain a composite admixture;

[0061] S4: Preparation of component B

[0062] By weight, 275 parts of cement, 90 parts of fly ash, 650 parts of crushed stone and 550 parts of river sand were added to a concrete mixer, stirred for 25 minutes, and fully dispersed and mixed, then 15 parts of polycarboxylate water reducer and 225 parts of water were added to the concrete mixer, and stirred for 20 minutes and fully mixed, and finally, 170 parts of rice husk ash, 75 parts of basalt fiber, 40 parts of chopped basalt fiber and 80 parts of calcium sulfate whisker were added to the concrete mixer, and stirred for 25 minutes to obtain component B;

[0063] S5: Mix component A and component B and add composite admixture

[0064] The above component A is added to the component B in a mass ratio of 1:9, and then 200 parts by weight of the above composite admixture are added, and the mixture is fully stirred and mixed to obtain high-strength frost-resistant concrete.

[0065] Example 3

[0066] A preparation process of high-strength frost-resistant concrete comprises the following steps:

[0067] Add thiosemicarbazide and salicylaldehyde to methanol at a molar ratio of 1:1.4, stir to dissolve, and mix thoroughly to obtain a mixed solution, wherein the solid-liquid ratio of thiosemicarbazide to methanol is 1g:30mL, then heat the mixed solution at 80°C, stir to condense and crystallize, filter and collect the precipitated crystals, wash and dry to obtain powdery crystals, then dissolve phosphomolybdic acid in deionized water at a solid-liquid ratio of 1g:35mL, add the powdery crystals, disperse by ultrasonic vibration for 40min, add octylphenyl polyoxyethylene ether, continue ultrasonic dispersion for 20-30min, and obtain the separated crystals. Dispersion, for standby use, wherein the mass ratio of powdered crystals to phosphomolybdic acid is 1.5:1, and the mass ratio of octylphenyl polyoxyethylene ether to phosphomolybdic acid is 1:20, and then the acrylic acid is heated to 60°C, and then sodium hydroxide solution and ammonium persulfate are added while stirring, and the reaction is performed for 12 hours to obtain a sodium polyacrylate solution, for standby use, wherein the molar ratio of sodium hydroxide to acrylic acid is 3:1, and the concentration of the sodium hydroxide solution is 0.3 mol / L, and finally, the dispersion is added to the sodium polyacrylate solution at a volume ratio of 1:12, and then dilute sulfuric acid is added to adjust the pH to 6.5, and stirred for 1.5 hours to obtain component A;

[0068] S2: Preparation of urea-formaldehyde resin prepolymer

[0069] Urea and 35% formaldehyde solution were mixed and stirred in a mass ratio of 1:3 to dissolve, and triethanolamine was added to adjust the pH to 9, and then heated and stirred at 80°C for 50 hours to reflux to obtain a urea-formaldehyde resin prepolymer;

[0070] S3: Preparation of composite admixtures

[0071] Polyvinyl alcohol and epoxy resin were added to deionized water at a mass ratio of 1:5:80, stirred for 30 minutes, and then n-octanol was added and placed in a high-speed dispersing homogenizer for 40 minutes at a rate of 6000r / min to obtain an emulsion, wherein the mass ratio of n-octanol to epoxy resin was 1:45, and then the urea-formaldehyde resin prepolymer and the emulsion were stirred at a rate of 500r / min for 2 hours at a volume ratio of 1:16, fully mixed, and then heated to 80°C for 4 hours to obtain intermediate A. After that, NH4Cl was added to the intermediate A to adjust the pH to 4, and then deionized water and resorcinol were added, stirred for 3 hours, and solidified to obtain intermediate B, wherein the volume ratio of deionized water to intermediate A was 1:5, and the solid-liquid ratio of resorcinol to deionized water was 1g:25mL. Finally, sodium carbonate solution was added to the intermediate B to adjust the pH to 8, and the mixture was naturally cooled to room temperature and allowed to stand for stratification, the upper aqueous phase was removed, and then the lower precipitate was washed with deionized water for 4 times, and dried to obtain a composite admixture;

[0072] S4: Preparation of component B

[0073] By weight, 320 parts of cement, 100 parts of fly ash, 700 parts of crushed stone and 600 parts of river sand were added to a concrete mixer, stirred for 30 minutes, and fully dispersed and mixed, then 20 parts of polycarboxylate water reducer and 300 parts of water were added to the concrete mixer, and stirred for 25 minutes and fully mixed, and finally, 180 parts of rice husk ash, 80 parts of basalt fiber, 45 parts of chopped basalt fiber and 95 parts of calcium sulfate whisker were added to the concrete mixer, and stirred for 30 minutes to obtain component B;

[0074] S5: Mix component A and component B and add composite admixture

[0075] The above component A is added to the component B at a mass ratio of 1:10, and then 220 parts by weight of the above composite admixture are added, and the mixture is fully stirred and mixed to obtain high-strength frost-resistant concrete.

[0076] Performance Test:

[0077] 1. Concrete compressive strength test. The concrete mixed in each embodiment was made into a test piece of 100 mm × 100 mm × 100 mm. According to GB / T50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete", the compressive strength of each test piece at 28 days was tested. The test results are shown in Table 1 below;

[0078] 2. Concrete frost resistance durability test. After the test block with an age of 28 days is saturated with water, the concrete mixed in each embodiment is made into a cubic test piece of 100mm×100mm×100mm. According to the slow freezing method of GB / T50082-2009 "Standard for Test Methods of Long-term Performance and Durability of Ordinary Concrete", each test piece is subjected to 100 freeze-thaw treatments. After the freeze-thaw treatment, the mass loss rate and compressive strength loss rate of each test piece are detected. When the compressive strength decreases by no more than 25% and the mass loss does not exceed 5%, it indicates that the frost resistance is good. The test results are shown in Table 1 below.

[0079] Table 1: Summary of performance test results of Examples 1-3

[0080]

[0081] Comparative Example 1

[0082] The difference between this comparative example and Example 1 is that step S1 is removed, and component A in step S5 is replaced by an equal amount of component B, and then a performance test is performed according to the performance test method in Example 1, and the results are shown in Table 2 below.

[0083] Table 2: Comparative Example 1 and Example 1 Performance Test Results Comparison Table

[0084]

[0085] As shown in Table 2 above, in Comparative Example 1, after component A is not added, the 28d compressive strength of the prepared concrete is about 65.13 MPa, which is less than that of Example 1, and the mass loss and compressive strength loss measured after freeze-thaw test are about 1.04% and 16.3%, respectively, which are both greater than that of Example 1. It can be seen that by first dissolving thiosemicarbazide and salicylaldehyde together in methanol, heating the reaction and condensing the crystals to obtain powdered crystals, and then adding the powdered crystals to an aqueous solution of phosphomolybdic acid, and adding octylphenyl polyoxyethylene ether to uniformly disperse to prepare a dispersion, and finally adding the dispersion to a sodium polyacrylate solution to obtain component A, and adding component A to concrete, its chain sodium polyacrylate has a dispersing effect, which can promote the dispersion and hydration of concrete, and the hybrid polyhedral structure of the powdered crystals and phosphomolybdic acid as an adsorption nucleation center, establishes multiple crystallization sites, and makes the particle size of CSH gel and needle-shaped ettringite uniform and dense, thereby improving the compressive strength and frost resistance of concrete.

[0086] Comparative Example 2

[0087] The difference between this comparative example and Example 1 is that steps S2 and S3 are removed, and the composite admixture in step S5 is removed, and then the performance test is carried out according to the performance test method in Example 1, and the results are shown in Table 3 below.

[0088] Table 3: Comparison of performance test results between Comparative Example 2 and Example 1

[0089] Test items Mass loss (%) Compressive strength loss (%) Example 1 0.32 7.8 Comparative Example 2 1.10 17.1

[0090] As shown in Table 3 above, in Comparative Example 2, after no composite admixture is added, the mass loss and compressive strength loss of the prepared concrete after freeze-thaw test are respectively about 1.10% and 17.1%, both of which are greater than those in Example 1. It can be seen that by first mixing urea and formaldehyde solution to form a urea-formaldehyde resin prepolymer, then adding epoxy resin and polyvinyl alcohol into deionized water, dispersing them into an emulsion at high speed, and then mixing the urea-formaldehyde resin prepolymer and the emulsion and heating them to react to form a composite admixture, after the composite admixture is added to the concrete, when the concrete is subjected to freeze-thaw, the admixture can be broken in time to release the repair agent to fill the microcracks caused by freeze-thaw of the concrete, thereby further improving the frost resistance and durability of the concrete.

[0091] Comparative Example 3

[0092] The difference between this comparative example and Example 1 is that the rice husk ash, basalt fiber, chopped basalt fiber and calcium sulfate whisker in step S4 are removed, and then the performance test is carried out according to the performance test method in Example 1, and the results are shown in Table 4 below.

[0093] Table 4: Comparative Example 3 and Example 1 Performance Test Results Comparison Table

[0094]

[0095] Comparative Example 4

[0096] The difference between this comparative example and Example 1 is that the chopped basalt fibers and calcium sulfate whiskers in step S4 are replaced with an equal amount of basalt fibers, and then a performance test is performed according to the performance test method in Example 1, and the results are shown in Table 5 below.

[0097] Comparative Example 5

[0098] The difference between this comparative example and Example 1 is that the basalt fiber and calcium sulfate whisker in step S4 are replaced by an equal amount of chopped basalt fiber, and then a performance test is performed according to the performance test method in Example 1, and the results are shown in Table 5 below.

[0099] Comparative Example 6

[0100] The difference between this comparative example and Example 1 is that the basalt fiber and the chopped basalt fiber in step S4 are replaced by an equal amount of calcium sulfate whiskers, and then a performance test is performed according to the performance test method in Example 1, and the results are shown in Table 5 below.

[0101] Table 5: Comparison of performance test results of Comparative Examples 4-6 and Example 1

[0102] Test items Mass loss (%) Compressive strength loss (%) Example 1 0.32 7.8 Comparative Example 4 0.83 11.6 Comparative Example 5 0.92 13.3 Comparative Example 6 0.78 9.8

[0103] As shown in Tables 4 and 5 above, in Comparative Example 3, after no rice husk ash, basalt fiber, chopped basalt fiber and calcium sulfate whisker were added, the 28d compressive strength of the prepared concrete was about 46.35 MPa, which was much lower than that of Example 1. It can be seen that adding rice husk ash, basalt fiber, chopped basalt fiber and calcium sulfate whisker to concrete is beneficial to improving the compressive strength of concrete.

[0104] In contrast, in Comparative Examples 4-6, only single basalt fiber, single chopped basalt fiber and single calcium sulfate whisker were added to obtain concrete, and the mass loss and compressive strength loss measured by freeze-thaw test were greater than those in Example 1. It can be seen that the simultaneous addition of basalt fiber, chopped basalt fiber and calcium sulfate whisker is beneficial to improving the interface bonding between aggregate and cement paste, optimizing the internal pore structure of concrete, forming a denser microstructure, reducing the penetration of water from the environment into the interior of the concrete, and reducing the frost heave pressure caused by the freezing of free water in the concrete, thereby improving the anti-freeze durability of the concrete.

[0105] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A process for preparing high-strength frost-resistant concrete, characterized in that: The steps include: S1: Preparation of component A S1.1: Add thiosemicarbazide and salicylaldehyde to methanol in a molar ratio of 1:(1.2-1.4), stir to dissolve, and mix thoroughly to obtain a mixed solution; S1.2: heating the mixed solution at 70-80°C while stirring to condense and crystallize, collecting the precipitated crystals by filtration, washing and drying to obtain powdery crystals; S1.3: Dissolve phosphomolybdic acid in deionized water at a solid-liquid ratio of 1 g: (25-35) mL, add the above powdered crystals, disperse by ultrasonic vibration for 30-40 min, add octylphenyl polyoxyethylene ether, and continue ultrasonic dispersion for 20-30 min to obtain a dispersion; S1.4: Heat acrylic acid to 50-60°C, then add sodium hydroxide solution and ammonium persulfate while stirring, and react for 10-12 hours to obtain a sodium polyacrylate solution; S1.5: Add the above dispersion to the above sodium polyacrylate solution in a volume ratio of 1:(8-12), then add dilute sulfuric acid to adjust the pH to 5.5-6.5, and stir for 1-2 hours to obtain component A; S2: Preparation of urea-formaldehyde resin prepolymer Mix urea and 35% formaldehyde solution in a mass ratio of 1: (2.5-3.5) and stir to dissolve, then add triethanolamine to adjust the pH to 8-9, then heat and stir under reflux at 70-80° C. for 40-50 hours to obtain a urea-formaldehyde resin prepolymer; S3: Preparation of composite admixtures Polyvinyl alcohol, epoxy resin, deionized water and n-octanol are dispersed and mixed at high speed, and then the urea-formaldehyde resin prepolymer is added, fully mixed and heated for reaction, and then NH4Cl, deionized water and resorcinol are added, stirred and solidified, and finally sodium carbonate solution is added, and the composite admixture is obtained after standing and stratifying, washing and drying; S4: Preparation of component B Mixing cement, fly ash, crushed stone, river sand, polycarboxylate-based water reducer, water, rice husk ash, basalt fiber, chopped basalt fiber and calcium sulfate whisker to obtain component B; S5: Mix component A and component B and add composite admixture The above component A is added to component B in a mass ratio of 1:(8-10), and then the above composite admixture is added, and the mixture is fully stirred to obtain high-strength frost-resistant concrete.

2. The process for preparing high-strength frost-resistant concrete according to claim 1, characterized in that: S3 specifically includes the following steps: S3.1: Add polyvinyl alcohol and epoxy resin into deionized water in a mass ratio of 1: (3-5): (60-80), stir for 20-30 min, add n-octanol and place in a high-speed dispersing homogenizer and disperse at a rate of 5000-6000 r / min for 30-40 min to obtain an emulsion; S3.2: The urea-formaldehyde resin prepolymer prepared in step S2 and the above emulsion are stirred at a rate of 400-500 r / min for 1-2 h in a volume ratio of 1:(10-16), and then heated to 70-80°C for reaction for 3-4 h to obtain intermediate A; S3.3: Add NH4Cl to the intermediate A, adjust the pH to 3-4, then add deionized water and resorcinol, stir for 2-3 hours, and solidify to obtain intermediate B; S3.4: Add sodium carbonate solution to the intermediate B to adjust the pH to 7-8, cool naturally to room temperature and stand to separate the layers, remove the upper aqueous phase, then wash the lower precipitate with deionized water 3-4 times, and dry to obtain a composite admixture.

3. The preparation process of a high-strength frost-resistant concrete according to claim 2, characterized in that: S4 specifically includes the following steps: S4.1: Add cement, fly ash, crushed stone and river sand into a concrete mixer and stir for 20-30 minutes to fully disperse and mix; S4.2: Add polycarboxylate water reducer and water into the concrete mixer and continue stirring for 15-25 minutes to mix thoroughly; S4.3: Add rice husk ash, basalt fiber, chopped basalt fiber and calcium sulfate whisker into a concrete mixer and continue mixing for 20-30 minutes to obtain component B.

4. The preparation process of a high-strength frost-resistant concrete according to claim 1, characterized in that: The solid-liquid ratio of thiosemicarbazide to methanol is 1g:(20-30)mL.

5. The process for preparing high-strength frost-resistant concrete according to claim 1, characterized in that: The mass ratio of powdery crystals to phosphomolybdic acid is (1.1-1.5):1, the mass ratio of octylphenyl polyoxyethylene ether to phosphomolybdic acid is 1:(16-20), the molar ratio of sodium hydroxide to acrylic acid is (1-3):1, the solid-liquid ratio of ammonium persulfate to sodium hydroxide solution is 1g:(55-65)mL, and the concentration of the sodium hydroxide solution is 0.1-0.3mol / L.

6. The process for preparing high-strength frost-resistant concrete according to claim 2, characterized in that: The mass ratio of n-octanol to epoxy resin is 1:(35-45).

7. The process for preparing high-strength frost-resistant concrete according to claim 2, characterized in that: The volume ratio of deionized water to intermediate A is 1:(3-5), and the solid-liquid ratio of resorcinol to deionized water is 1g:(15-25)mL.

8. The process for preparing high-strength frost-resistant concrete according to claim 3, characterized in that: Calculated by weight, component B includes: 230-320 parts of cement, 80-100 parts of fly ash, 600-700 parts of crushed stone, 500-600 parts of river sand, 160-180 parts of rice husk ash, 70-80 parts of basalt fiber, 35-45 parts of chopped basalt fiber, 65-95 parts of calcium sulfate whisker, 10-20 parts of polycarboxylate water reducer and 150-300 parts of water.

9. The process for preparing high-strength frost-resistant concrete according to claim 1, characterized in that: The amount of the composite admixture added is 180-220 parts by weight.

10. A high-strength frost-resistant concrete, characterized in that: It is prepared by the preparation process of a high-strength frost-resistant concrete as described in any one of claims 1 to 9.